2015
DOI: 10.1002/ajmg.a.37298
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characteristics of craniosynostosis in Hungary

Abstract: Craniosynostosis, the premature closure of cranial sutures, is a common craniofacial disorder with heterogeneous etiology and appearance. The purpose of this study was to investigate the clinical and molecular characteristics of craniosynostoses in Hungary, including the classification of patients and the genetic analysis of the syndromic forms. Between 2006 and 2012, 200 patients with craniosynostosis were studied. Classification was based on the suture(s) involved and the associated clinical features. In syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The incidence of syndromic craniosynostosis was 9.2% in Sloan et al ’s[ 8 ] study, 20.5% in Oliveira et al ’s[ 9 ] study, 6% in Zakhary et al ’s [ 10 ] study, 12% in Bessenyei et al ’s[ 11 ] study, and 11.67% in our study.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The incidence of syndromic craniosynostosis was 9.2% in Sloan et al ’s[ 8 ] study, 20.5% in Oliveira et al ’s[ 9 ] study, 6% in Zakhary et al ’s [ 10 ] study, 12% in Bessenyei et al ’s[ 11 ] study, and 11.67% in our study.…”
Section: Discussionsupporting
confidence: 44%
“…[ 9 ] Zakhary et al [ 10 ] in his paper observed that there were 73% men and 27% women. Bessenyei et al [ 11 ] in his paper observed that the sagittal suture was the most commonly involved, followed by the coronal, metopic, and lambdoid sutures. Kolar et al [ 12 ] in his paper noted a much higher incidence of metopic synostosis than has been reported in the traditional clinical literature.…”
Section: Discussionmentioning
confidence: 99%
“…2 We present the clinical findings of a patient with SP diagnosed inutero due to a variant in FRFR2 gene. [8][9][10][11][12][13] Although most cases are diagnosed in their neonatal stage, prenatal diagnosis is possible. Three-dimensional obstetric ultrasound is the first-line diagnostic tool for suspected PS, being useful to verify suture closure in the third trimester of pregnancy for the most severe cases 14 although the diagnosis with lower gestational ages has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This targeted approach identifies a causative variant in approximately 71-75% of probands with syndromic craniosynostosis, but rarely in those with nonsyndromic unisutural craniosynostosis. 1,5,6 Additional genes have been identified more recently, associated with a range of autosomal dominant, autosomal recessive, and X-linked craniosynostoses; most notably, TCF12 (coronal), ERF (sagittal, lambdoid), FREM1 (metopic), and EFNA4 (coronal). 3,[7][8][9] The relative causative contributions of these genes in a clinically ascertained cohort from a multidisciplinary craniofacial clinic is unclear.…”
Section: Introductionmentioning
confidence: 99%